Radio resource management for WLAN networks through power control - Dafalla, Z. I.; Murthy, M. B. R.; Clement, S.; Tan, T. C. T. (IEEE Xplore, 2005)
Wireless Local Area Networks (WLANs) based on IEEE 802.11 standard have been rapidly growing. With limitations of the standard and rapid increase in wireless application demand, the air interface acts as bottleneck even in high-speed WLAN standards such as IEEE 802.11a and 802.11g with expected data transmission rates of up to 54 Mbps. To improve the overall performance of IEEE 802.11 WLAN under large deployment and heavy application demand environment, Radio Resource Management (RRM) algorithms based on power control have been investigated and tested through simulation. The results show that controlling the wireless terminal's (WT) transmitter power to an optimum power level is important. This results into an increased data throughput in a WLAN network and when the transmitter power level of a WT is increased beyond the optimum power level, the throughputs drop drastically no matter how high the WT's transmitter power may be increased.